JACIE : a scripting language for internet-based multimedia collaborative applications [microfilm] - Abdul Samad Ismail, 1930-; Mohd. Sarofil Abu Bakar; Nor Haliza Madros (Swansea : University of Wales, 2001)
Thesis (Doktor Falsafah)) - University of Wales, 2001